2020
DOI: 10.1093/cid/ciaa1338
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 RNA in Plasma Is Associated With Intensive Care Unit Admission and Mortality in Patients Hospitalized With Coronavirus Disease 2019

Abstract: The clinical significance of SARS-CoV-2 RNA in the circulation is unknown. In this prospective cohort study, we detected viral RNA in the plasma of 58/123 (47%) patients hospitalized with COVID-19. RNA was detected more frequently, and levels were higher, in patients who were admitted to the ICU and/or died.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 10 publications
6
73
3
Order By: Relevance
“…Nasopharyngeal viral shedding peaks shortly before the onset of symptoms and declines thereafter, making the timing of sampling relative to symptom onset an important determinant of test performance [ 3 , 162 ]. Viral load in the lungs or plasma may be more reflective of disease progression [ 163 ]; the detection of viral RNA in plasma (“RNAemia”) correlates with more severe illness [ 164–168 ]. Some studies have correlated nasopharyngeal viral load at the time of presentation with clinical outcomes and the ability to isolate SARS-CoV-2 in culture [ 157 , 169–173 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Nasopharyngeal viral shedding peaks shortly before the onset of symptoms and declines thereafter, making the timing of sampling relative to symptom onset an important determinant of test performance [ 3 , 162 ]. Viral load in the lungs or plasma may be more reflective of disease progression [ 163 ]; the detection of viral RNA in plasma (“RNAemia”) correlates with more severe illness [ 164–168 ]. Some studies have correlated nasopharyngeal viral load at the time of presentation with clinical outcomes and the ability to isolate SARS-CoV-2 in culture [ 157 , 169–173 ].…”
Section: Diagnosismentioning
confidence: 99%
“…In this context, circulating SARS-CoV-2 RNA (RNAemia) has been highlighted as a promising prognostic biomarker in hospitalized COVID-19 patients, as it is associated with disease severity 7 and mortality [8][9][10] , with an estimated prevalence of 10% (95% CI 5-18%, random effects model) 7 . Further, we hypothesized that the acute and profound alterations in the innate and adaptive immune system in COVID-19 patients 3,[11][12][13] , especially in RNAemic patients [14][15][16][17][18] , will be accompanied by marked changes in the circulating proteome and interactome and that the proteome in COVID-19 patients will highlight mechanistically relevant signatures and trajectories, when compared to non-COVID-19 sepsis and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from a possible role in disease pathogenesis, blood–borne viral RNA could also be an important indicator of lung tissue breakdown leading to release of intact virions, viral proteins and nucleic acids, or infected cells into the bloodstream. Along these lines, a few groups have found that the detection of SARS-CoV-2 RNA in plasma (SARS-CoV-2 RNAemia) is associated with severe disease [ 45 ▪ , 46 ▪ , 47 , 48 ▪ 50 ▪ ], although to inconsistent degrees. The inconsistency in proportion of patients with plasma RNA and the amount of plasma RNA is likely due to differences in definitions of disease severity and in the RT-PCR methods used.…”
Section: Sensitive Methods For Measuring Viral Rnamentioning
confidence: 99%